KOLABORASI ORGANISASI PEMERINTAH DALAM PENERTIBAN PARKIR LIAR DI KOTA MAKASSAR - Ikhsan, Nurul Ansaria; Malik, Ihyani; Khaerah, Nur (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
This study aims to how the collaboration of government organisations in controlling illegal parking in Makassar City. This type of research uses qualitative methods. The results of this study indicate that Collaboration carried out by the Department of Transportation, Head of the Pamung Praja Police Unit for Makassar City, and PD Parking Makassar Raya, such as joint meetings held 2-3 times a month, still needs to be improved because we can see there are still many problems that often occur in the field, such as the number of vehicles which are parked on the side of the road, apart from that the joint operations carried out between these agencies have still not been resolved because of the related parties who have not maximized their operating schedules and the lack of signs on the road and the process of implementing management and evaluation between these agencies has been effective, but this authority has not run smoothly, such as the regulation of parking lots and prosecution of motorists has not yet become a deterrent effect for the community, so the Department of Transportation must be more assertive in dealing with this problem and supporting factors in coordination between government agencies in dealing with illegal parking in the city of Makassar, the aspect is cooperation between institutions, communities and well-established communication between related institutions in handling illegal parking cases. The inhibiting factors in coordination between government agencies in dealing with illegal parking in Makassar City are inadequate facilities, infrastructure and human resources which are one of the inhibiting factors in controlling illegal parking in Makassar City.